Modern challenges of iodine nutrition: vegan and vegetarian diets - Laura Croce; Laura Croce; Mario Rotondi; Mario Rotondi; Rosaria Maddalena Ruggeri (Frontiers in Endocrinology)
Vegetarian diets are gaining popularity worldwide, especially among women and in the younger part of the population, rising some concerns for the risk of inadequate iodine requirements if the diet is not correctly planned. Indeed, subjects under vegetarian dietary regimens, mainly the vegan ones, are at risk of developing both iodine deficiency and excess, due to lack of animal-derived foods on the one hand, and to the use of vegan alternatives (such as seaweed) and over-the-counter supplements on the other hand. Women in childbearing age and children are particularly vulnerable to the adverse thyroid consequences. Thus, this paper aims to provide some practical information to achieve adequate iodine intake and avoid adverse effects on thyroid in this population.